The Effect of Hustle Culture on Job Satisfaction Among Startup Workers in Indonesia: Pengaruh Hustle Culture Terhadap Kepuasan Kerja pada Pekerja Perusahaan Rintisan di Indonesia - Khalida Salsabila Aziz; Abdhy Aulia Adnans (Talenta Publisher, 2023)
This research aims to acknowledge the hustle culture's effect on startup workers' job satisfaction in Indonesia. The research method used in this research is descriptive quantitative with a purposive sampling method. The sample of this research is 351 subjects. Data collection uses Likert scales, namely JDI (Job Descriptive Index) and Hustle Culture Scale. The method of data analysis is a simple regression analysis method. Results from the research showed a negative effect of hustle culture on job satisfaction with a negative direction of the effect. The result concluded that the higher the hustle culture, the lower the job satisfaction.